(3GdeMGSHI GdJMdjdjI (B:s (3OQhS hJeGQjf eMdhdI (B/s - (3HOjSj, agjeIs ((3GdLRGFQ(B: s (3OGQ GdgOi ddWHGYI hGdfTQ hGdJhRjY(B, s, 2013)
(3jVe CSGSjGJ GdeMGSHI GdJMdjdI, GdJMdjd GdhXjaj ddCYHGA, eMGSHI GdehGO, MGdGJ NGUI, GdeYGdLI GdeMGSHjI ddCYHGA GdeHGTQI hGdCYHGA ZjQ GdeHGTQI WQjbI GdCbSGe GdeJLGfSI, WQjbI GdCYHGA GdKGHJI hGdeJZjQI, WQjbI GdJMejd GdYbdGfj ddCYHGA GdKGHJI, WQjbI GdJcGdja GdJbOjQjI, WQjbI GdJcGdja GdgGeTjI (B.s
(3GdeQGLY U(B.297s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdJMdjdjIs